Medical textiles. Issue 1 (2nd April 2020) - Morris, H.; Murray, R.
Abstract: Medical textiles is an emerging specialist field within the textile industry showing substantial growth in the amount of research attention it has attracted over the past ten years and it is becoming a rapidly-growing part of the textile industry. Much of the stimulus for its growth has arisen from the establishment of nanotechnology enabling the incorporation of nanoparticles into fibre-forming polymers before spinning into filament form, nanofinishing treatments allowing nanomaterials to be added to fabrics and electrospinning enabling the preparation of fibre-forming polymers into nanofibres and also the incorporation of nano-particulate agents into the electrospun nanofibres. The performance of the emergent materials, particularly of those relating to antimicrobial action, have shown substantial improvement over many of their traditionally-prepared counterparts, not least in relation to their durability, which is typically high for those where the nanoparticles were blended into the polymer prior to spinning, or where covalent bonding to the fibre surface was involved. Absorbable polymer implants in fibrous, nano-fibrous and continuous-filament form have also been the focus of considerable research attention because they reduce/eliminate the need for further invasive surgery for their removal, whilst strong, durable textile structures whose performance can be modelled and predicted, have been and are being developed for the replacement of tendons and for the construction of pressure garments and wound dressings. This review serves to categorise the various domains, explore the range of textile materials and devices either emerging or now in use in healthcare and offers recommendations for future project areas to move healthcare and the medical textile sector forward. A critical review is provided of single-use items of PPE and the lack of preparedness for the recent pandemic; solutions for circumventing the shortcomings of single-use items are presented.